Pripovedne značilnosti sodobne slovenske tržaške kratke proze (1990-2013) - Umek, Loredana (Jezik in slovstvo, 2015)
The article analyses the short story narrative of contemporary Slovenian writers from Trieste published in the last twenty years in the Trieste region. It deals with the authors' narrative worlds as well as the motivic-thematic and material-conceptual aspects that formally and stylistically define the characteristics of Trieste short stories. The works in question form a corpus of sophisticated literary texts that shed light not only on events and life in Trieste, but also on the existential crises and dilemmas of modern man. The article does not treat the short prose works of Boris Pahor, Alojz Rebula and Vladimir Bartol in detail, as their works have already been extensively monographically profiled in keySlovenian and Trieste literary studies.
Keywords: Pahor, Boris, 1913-; Trst; Rebula, Alojz, 1924-; Bartol, Vladimir, 1903-1967; Slovene literature; slovenska književnost; slovenska zamejska književnost; kratka proza; 1990-2013